Characterization of Genetic Diversity Among Cucumis Accessions Based on Morphological and Phytochemical Characters - Aryakia, Elyas; Naghavi, Mohammad Reza (Acta Natura et Scientia, 2022)
The genus Cucumis L. of the Cucurbitaceae family is widely cultivated all over the world. Despite wide distribution and consumption, there is little information for the assessment of genetic diversity among Iranian Cucumis species. In this study, genetic diversity among 21 accessions of Iranian Cucumis species (C. sativus and C. melo) was assessed using 20 morphological characters of fruit and leaf and 4 phytochemical characters. High phytochemical and morphological diversity at intra- and interspecific levels were revealed among Cucumis species, which reflects the industrial potential of Iranian accessions for breeding and commercial usage. The grouping pattern of genetic diversity was constructed using the UPGMA dendrogram. The results of the grouping pattern revealed high efficiency of morphological and phytochemical characteristics for uncovering the genetic diversity of Cucumis accessions. Moreover, using morphological characters, cucumbers were separated according to their ecological zones. Considerable amounts of phytochemical properties were revealed among Iranian Cucumis accessions, which were comparable to those reported in other studies. Furthermore, unlike Total phenol content and total flavonoid content, melons showed more total sugar and DPPH radical scavenging activity than cucumbers. These results could be important for Cucumis gene bank management, agriculture, and breeding programs.